Torrefaction of Napier Grass and Oil Palm Petiole Waste Using Drop-Type Fixed-Bed Pyrolysis Reactor - Saadon, S.Z.A.H. (MDPI, 2022)
The torrefaction process in the preparation of energy materials has garnered a lot of attention and has been investigated as a means of improving biomass solid fuels. The aim of this study is to study the effect of the temperature and holding time of two biomass samples: wild Napier grass and oil palm petiole. The torrefied samples are operated in a pyrolysis reactor to replicate the torrefaction procedure. The temperature parameter ranges between 220 and 300â¦C while the holding time of the reaction parameter ranges from 10 to 50 min. It is found that with increasing temperature and time, the moisture content and number of O and H atoms decrease and also cause both mass and energy yield to decrease. It is found that the calorific value and the energy density increase with both parameters, which shows that optimization is needed for better solid fuel production. Between the two parameters, temperature changes have more significant effects on the torrefied samples. The optimized temperature and time are found to be 260â¦C and 30 min, respectively. The usage of the pyrolysis reactor for the torrefaction reaction has been proven to serve as a good option due to similar product characteristics and equivalent results. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.